An Interpretation of Petrotectonic Assemblage West of Western Himalayan Syntaxis in Dir District and Adjoining Area in Northern Pakistan - Butt, Khursheed Alam; Chaudhry, Muhammad Nawaz; Ashraf, M (Journal of Himalayan Earth Sciences, 1980)
A review of the geology of areas west of western syntaxial bend of Himalayas in Dir district and adjoining areas of northern Pakistan is presented. Several geotectonic regimes have been recognized and it is proposed that the well-known Indus ophiolite suture in this area is represented by amphibolite/ophiolite belt of Dir. These ophiolites are thought to have generated in m ocean and that their emplacement involved initially an ocean-continent type of plate interaction followed much later by continent-continent collision.